Assessing intervention effectiveness at promoting voluntary conservation practice adoption in agrienvironments. Issue 1 (16th January 2023) - Read, Daniel J.; Wainger, Lisa
Abstract: Although implementing conservation practices on private farms and forests can produce substantial environmental benefits, these practices are not being adopted widely enough to result in measurable improvements at regional scales. Researchers have investigated the production and program factors influencing producer choices to voluntarily adopt these practices. However, the findings of reviews are inconsistent, raising questions about review methods, including the omission of relevant variables. Further, applying lessons from past work to promote adoption is difficult because many reviews investigated dispositional or demographic variables that practitioners and policy makers cannot directly observe or influence. We conducted a new review of 146 empirical studies that tested the effects of different interventions (e.g., financial incentives, outreach events, and nudges) on increasing the likelihood of producers adopting conservation practices. We conducted a metaregression of quantitative studies from diverse disciplines that filtered studies by quality (i.e., use of randomization and clear analysis reporting). We synthesized these results with a thematic analysis of qualitative studies on producer perspectives about conservation practices. Financial incentives had the strongest evidence of increasing producers' likelihood of adopting conservation practices (odds ratio 1.86, p < 0.05). However, this effect was only apparent after filtering by study quality, which also improved model fit and identified significant regional differences (odds ratio –1.69, p < 0.01). The thematic review of qualitative studies revealed that peer groups may be successful in reinforcing adoption behaviors due to homophily effects and that financial incentives not only offset implementation costs but also mitigated perceived risks of adoption. Given the problems we encountered in testing hypotheses about the magnitude of variability explained by intervention types and practice characteristics, we recommend additional experimental and longitudinal work that accounts for financial incentives and pairs qualitative and quantitative data to clarify relationships between program design and practice adoption rates. Abstract : Evaluación de la efectividad de las intervenciones en la promoción de la adopción de prácticas de conservación voluntaria en los agroecosistemas Resumen: Aunque la implementación de prácticas de conservación en granjas y bosques privados puede producir beneficios ambientales sustanciales, estas prácticas no se adoptan lo suficiente como para tener mejoras medibles en escalas regionales. Los investigadores han estudiado los factores de producción y programación que influyen sobre la elección de los productores de adoptar voluntariamente estas prácticas. Sin embargo, los hallazgos de las revisiones son inconsistentes, lo que genera preguntas sobre los métodos de revisión, incluyendo la omisión de variables relevantes. Además, es complicado aplicar lo aprendido en trabajos previos para promover la adopción porque muchas revisiones investigaron las variables demográficas y de disposición que los practicantes y los formuladores de políticas no pueden observar o influir directamente. Realizamos una nueva revisión de 146 estudios empíricos que analizaron los efectos de diferentes intervenciones (p. ej.: incentivos económicos, eventos de divulgación, estímulos) sobre el incremento de la probabilidad de que los productores adopten prácticas de conservación. Realizamos la meta regresión de estudios cuantitativos a partir de diferentes disciplinas que filtraron los estudios por calidad (uso de aleatorización y reporte claro de análisis). Sintetizamos estos resultados con un análisis temático de los estudios cualitativos sobre las perspectivas que tienen los productores de las prácticas de conservación. Los incentivos económicos contaron con la evidencia más sólida de incrementar la probabilidad de que los productores adoptaran prácticas de conservación (proporción de probabilidades 1.86, p < 0.05). Sin embargo, este efecto sólo fue aparente después de filtrar según la calidad del estudio, lo que también mejoró el ajuste del modelo e identificó diferencias regionales significativas (proporción de probabilidades ‐1.69, p < 0.01). La revisión temática de los estudios cualitativos reveló que los grupos de referencia pueden tener éxito en el refuerzo de los comportamientos de adopción debido a los efectos de homofilia y el hecho de que los incentivos económicos no sólo compensan los costos de implementación, sino también mitigan los riesgos percibidos de la adopción. Ya que nos encontramos con problemas en la prueba de la hipótesis sobre la magnitud de la variabilidad explicada por los tipos de intervención y las características de la práctica, recomendamos una experimentación adicional y trabajo longitudinal que explique los incentivos económicos y empareje los datos cualitativos y cuantitativos para clarificar las relaciones entre el diseño del programa y las tasas de adopción de las prácticas. 【摘要】: 虽然在私人农场和森林中实施保护措施可以产生巨大的环境效益, 但这些措施并没有得到广泛采用以在区域尺度上产生可观测的改善效果。研究者已分析了影响生产者选择义务采取这些措施的生产和规划因素。然而, 综述的结果之间存在分歧, 这引起了对综述方法的质疑, 包括忽略了相关变量等。此外, 从过去的工作中吸取经验教训以推动采取保护措施也面临困难, 因为许多综述调查了实践者和政策制定者不能直接观察或影响的秉性变量或人口统计学变量。因此, 我们对146项实证研究进行了新的综述, 这些研究测试了不同干预措施(例如, 经济激励措施、推广活动、动员措施)对提高生产者采取保护措施可能性的影响。我们对来自不同学科的定量研究进行了荟萃回归, 并通过质量(即采用随机化和明确的分析报告)对研究进行了过滤。我们进一步整合了这些结果与关于生产者对保护措施看法的定性研究的专题分析。结果表明, 经济激励提高生产者采取保护措施可能性的证据最强(优势比为1.86, p < 0.05)。然而, 这种效果只在过滤了研究质量后才明显, 这也提高了模型的拟合度, 并识别出显著的区域差异(优势比为‐1.69, p < 0.01)。定性研究的专题综述显示, 由于同质效应, 同伴群体可能成功地加强采取保护措施, 而经济激励不仅抵消了实施成本, 还减缓了采取行动所感知到的风险。鉴于我们在检验干预类型和实践特征所解释的变异程度的假设时遇到的问题, 我们建议开展更多的实验和纵向工作, 考虑经济激励措施, 并匹配定性和定量数据, 以厘清规划设计和采取实践比例之间的关系。【翻译:胡怡思;审校:聂永刚】